Sampling times and genotyping concerns in bioequivalence evaluation of branded and generic formulations - Zhao XY; Xu HM; Zhou Q (Dove Medical Press, 2013)
Xiao-Ying Zhao,1 Hui-Min Xu,2 Quan Zhou2 1The Medical Ethics Committee, 2Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of ChinaWe read with great interest the study by Del Tacca et al,1 who performed a comparative pharmacokinetic (PK) and pharmacodynamic (PD) evaluation of branded and generic formulations of meloxicam in healthy male subjects, and concluded that the two products can be used interchangeably in clinical practice. We especially appreciate their exploratory study on the PD/PK relationship which provides an important reference for bioequivalence studies of analgesics. However, we found two points worthy of discussion and we would like to share our perspectives in the following paragraphs.View original paper by Del Tacca and colleagues.